2020
DOI: 10.1002/adfm.202006186
|View full text |Cite
|
Sign up to set email alerts
|

Contact Modulated Ionic Transfer Doping in All‐Solid‐State Organic Electrochemical Transistor for Ultra‐High Sensitive Tactile Perception at Low Operating Voltage

Abstract: Ionic‐electronic coupling across the entire volume of conjugated polymer films endows organic electrochemical transistors (OECTs) with high transconductance (gm) and low operating voltage. However, OECTs utilize liquid electrolytes, which limit their long‐term operation, reproducibility, and integration while solid electrolytes typically result in inefficient ion transport. Here, a solid polymer electrolyte is shown that can facilitate good electrochemical response in conjugated polymers and yield high OECT pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 63 publications
2
67
1
3
Order By: Relevance
“…[25,33] Our group has previously reported that modifying of PEDOT:PSS with ionic liquids (IL), specifically 1-ethyl-3-methylimidazolium tricyanomethanide (EMIM TCM), enables the formation of enlarged and highly ordered PEDOT-rich domains, giving rise to high transconductance and volumetric capacitance. [12,34,35] This is due to the counter-ion exchange between PEDOT:PSS and EMIM TCM, leading to a structural transformation of PEDOT:PSS with closer PEDOT π-π packing and highly ordered fibrillar structures. The IL additives generally have three effects on PEDOT:PSS: (a) inducing phase separation and the formation of distinctive PEDOT and PSS domains; (b) enhancing the crystallinity of the PEDOT domains; (c) plasticizing the amorphous regions of PEDOT and PSS.…”
Section: Introductionmentioning
confidence: 99%
“…[25,33] Our group has previously reported that modifying of PEDOT:PSS with ionic liquids (IL), specifically 1-ethyl-3-methylimidazolium tricyanomethanide (EMIM TCM), enables the formation of enlarged and highly ordered PEDOT-rich domains, giving rise to high transconductance and volumetric capacitance. [12,34,35] This is due to the counter-ion exchange between PEDOT:PSS and EMIM TCM, leading to a structural transformation of PEDOT:PSS with closer PEDOT π-π packing and highly ordered fibrillar structures. The IL additives generally have three effects on PEDOT:PSS: (a) inducing phase separation and the formation of distinctive PEDOT and PSS domains; (b) enhancing the crystallinity of the PEDOT domains; (c) plasticizing the amorphous regions of PEDOT and PSS.…”
Section: Introductionmentioning
confidence: 99%
“…The ionic electrolyte fills these spatial network structures and flows freely to realize the ion migration. [78,79] In contrast to hydrogels, the crosslinking degree of this type of gel © 2022 Wiley-VCH GmbH is often larger, which makes the network structure more compact and reduces the water absorption and mobility of ions. Because the ionic electrolyte can only be fully mixed in a polar polymeric matrix with potentially high ionic conductivity, the choice of polymer depends on the polarity of the material.…”
Section: Polymer Matrices For Supercapacitive Interfacial Ionic Flexi...mentioning
confidence: 99%
“…(f) Real-time responses of the OECT pressure sensor to a flower and a grain of rice. Reproduced with permission from ref . Copyright 2020 Wiley-VCH.…”
Section: Modulation Strategies For Multifunctional Oectsmentioning
confidence: 99%
“…For an OECT, the ion injection flow can be well controlled by modulating the contact area between the electrolyte and the active channel. Following this strategy, microstructured pyramidal all-solid electrolyte is incorporated to fabricate contact modulated OECT pressure sensors . Ion injection to the channel increases upon the pressure loading, which results in enhanced doping/dedoping of the channel (Figure e).…”
Section: Modulation Strategies For Multifunctional Oectsmentioning
confidence: 99%